Transformasi Filsafat Islam di Mesir Modern: Dari Warisan Klasik ke Pemikiran Kontemporer - Atep Redi Rismawan; Lu’luil Maqnun; Hatob Hatob; M. Fadli Hasibuan; Rina Setyaningsih (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study addresses the Islamic reform movement in Egypt as a strategic and progressive response to both Western colonial domination and internal stagnation within the Muslim society. It analyzes the intellectual legacy of key reformers—Jamal al-Din al-Afghani, Muhammad Abduh, and Rashid Rida—who endeavored to reinterpret Islamic tenets through the lens of modern rationalism, scientific advancement, and updated political governance. Employing a historical-analytical perspective, this paper explores how these thinkers initiated transformative changes in religious exegesis, educational renewal, and Islamic legal discourse. The findings indicate that the reform movement was not merely a defensive reaction to modernity but a deliberate effort to revive ijtihad, cleanse Islamic belief from irrational traditions, and stimulate a socio-political revival grounded in Islamic ethical principles. Ultimately, this reformist legacy laid the groundwork for the evolution of modern Islamic thought across the Arab world and remains highly relevant in present-day discussions on Islam and modernity.